Treatment of verb anomia in aphasia: efficacy of self-administered therapy using a smart tablet. Issue 1 (2nd January 2016) - Lavoie, Monica; Routhier, Sonia; Légaré, Annie; Macoir, Joël
Abstract : Aphasia is a chronic condition that usually requires long-term rehabilitation. However, even if many effective treatments can be offered to patients and families, speech therapy services for individuals with aphasia often remain limited because of logistical and financial considerations, especially more than 6 months after stroke. Therefore, the need to develop tools to maximize rehabilitation potential is unquestionable. The aim of this study was to test the efficacy of a self-administered treatment delivered with a smart tablet to improve written verb naming skills in CP, a 63-year-old woman with chronic aphasia. An ABA multiple baseline design was used to compare CP's performance in verb naming on three equivalent lists of stimuli trained with a hierarchy of cues, trained with no cues, and not trained. Results suggest that graphemic cueing therapy, done four times a week for 3 weeks, led to better written verb naming compared to baseline and to the untrained list. Moreover, generalization of the effects of treatment was observed in verb production, assessed with a noun-to-verb production task. Results of this study suggest that self-administered training with a smart tablet is effective in improving naming skills in chronic aphasia. Future studies are needed to confirm the effectiveness of new technologies in self-administered treatment of acquired language deficits.